(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
After the determination of the Covid-19 virus as a pandemic, the education system began to look for an innovation for the process of teaching and learning activities. Moreover, the Circular no. 4 of 2020 from the Minister of Education and culture who recommends that all activities in educational institutions must keep a distance and all material delivery will be delivered at their respective homes. This prompted researchers to examine the role of teachers in the learning process during the pandemic at SD Negeri 112268 Gunung Lonceng. The research method uses a qualitative approach by conducting interviews with classroom teachers with a predetermined sample. It turns out that in practice the supporting and inhibiting factors greatly affect online learning (in the network) but are no less important than the role of the teacher. Without a classroom teacher, the learning process will not run well. The role of the classroom teacher is very influential on the educational process at the elementary level. The role of the classroom teacher is very dominant as a motivator, administrator and evaluator. A teacher who has a duty as a classroom teacher must have professional competence so that an effective and efficient learning process can be created and can overcome student problems in learning.